Measurements of In-Motion 802.11 Networking - Gass, Richard; Scott, James; Diot, Christophe (Proceedings of the Seventh IEEE Workshop on Mobile Computing System and Applications (HOTMOBILE 2006), 2006)
Wireless networking can support in-motion users by providing occasional opportunities to transmit and receive data. We measure the performance of UDP and TCP transfers between a car traveling at speeds from 5 mph to 75 mph, and an 802.11b access point. We analyze the impact of bandwidth and delay limitations in the backhaul network on the feasibility of in-motion transfer with typical Internet applications. We observe that in interference-free environments, a significant amount of data can be transferred using off-the-shelf equipment. We find that performance suffers mostly from network or application related problems instead of wireless link issues, i.e., protocols with handshakes, bandwidth limitations, and long round-trip times.